Measuring Spiritual Wellbeing—Seeking a Valid, Reliable, and Usable Measure - Nigel Pegram; Rebecca Loundar (Religions)
As part of an industry-based research partnership, the research team were asked to recommend a measure of spiritual wellbeing to assess client spiritual health and wellbeing and to determine programme efficacy. Existing measures were determined to be unsuitable for various reasons, including use in a multi-faith environment. The researchers developed a new Spiritual Wellbeing Scale, extending Fisher’s four domains to six distinct domains. For theoretical reasons, this tool assesses both importance and state. This paper introduces the instrument and assesses its psychometric properties. The assessments show the instrument to be both valid and reliable for a diverse population.